Engineering Support and Distribution of Palladium and Tin on MXene with Modulation of the d‐Band Center for CO‐resilient Methanol Oxidation. (12th October 2022) - Chen, Shufen; Liu, Ning; Zhong, Junjie; Yang, Rongliang; Yan, Bo; Gan, Liyong; Yu, Peng; Gui, Xuchun; Yang, Hongbin; Yu, Dingshan; Zeng, Zhiping; Yang, Guowei
Abstract: The efficiency of direct methanol fuel cell (DMFC) is largely determined by the activity and durability of methanol oxidation reaction (MOR) catalysts. Herein, we present a CO‐resilient MOR catalyst of palladium‐tin nano‐alloy anchored on Se‐doped MXene (PdSn0.5 /Se−Ti3 C2 ) via a progressive one‐step electrochemical deposition strategy. MOR mass activity resulting from Pd/Se−Ti3 C2 catalyst (1046.2 mA mg −1 ) is over 2‐fold larger than that of Pd/Ti3 C2, suggesting that the introduction of Se atoms on MXene might accelerate the reaction kinetics. PdSn0.5 /Se−Ti3 C2 with Se‐doping progress of MXene and the cooperated Pd−Sn sites has a superior MOR mass activity (4762.8 mA mg −1 ), outperforming many other reported Pd‐based catalysts. Both experimental results and theoretical calculation reveal that boosted electron interaction of metal crystals with Se‐doped MXene and optimized distribution of Pd−Sn sites can modulate the d band center, reduce adsorption energies of CO* at Pd site and enhance OH* generation at Sn site, resulting in highly efficient removal of CO intermediates by reaction with neighboring OH species on adjacent Sn sites. Abstract : Boosted electron interaction of metal nano‐alloy with Se‐doped MXene and optimized distribution of Pd−Sn sites on PdSn0.5 /Se−Ti3 C2 can modulate the d band center, decrease adsorption energies of CO* at Pd site and enhance OH* generation at Sn site, thus removing CO poisonous intermediates, and thereby significantly enhancing methanol oxidation reaction (MOR) efficiency and durability of the anodic catalyst for a direct methanol fuel cell (DMFC).